2016
DOI: 10.1002/chem.201601032
|View full text |Cite
|
Sign up to set email alerts
|

The Lanthanide Contraction beyond Coordination Chemistry

Abstract: The lanthanide contraction is conceptualized traditionally through coordination chemistry. Here we break this mold in a structural study of lanthanide ions dissolved in an amphiphilic liquid. The lanthanide contraction perturbs the weak interactions between molecular aggregates that drive mesoscale assembly and emergent behavior. The weak interactions correlate with lanthanide ion transport properties, suggesting new strategies for rare-earth separation that exploit forces outside of the coordination sphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 30 publications
6
63
0
Order By: Relevance
“…The amount of nitrate counterions (− e ) directly bound to each Ln III (+3 e ) is calculated to be around 2.9±0.5 for Ce 3+ and 2.9±0.6 for Yb 3+ , indicating that Ln III ions are nearly (∼97 %) charge neutralized by nitrates in organic phases. This decreases the electrostatic repulsion and allows the metalloamphiphile complexes to aggregate; a phenomenon that we recently investigated using small angle X‐ray scattering measurements . Very recently it was experimentally demonstrated that aggregates in metalloamphiphile‐in‐organic solutions are not strictly charge neutral …”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The amount of nitrate counterions (− e ) directly bound to each Ln III (+3 e ) is calculated to be around 2.9±0.5 for Ce 3+ and 2.9±0.6 for Yb 3+ , indicating that Ln III ions are nearly (∼97 %) charge neutralized by nitrates in organic phases. This decreases the electrostatic repulsion and allows the metalloamphiphile complexes to aggregate; a phenomenon that we recently investigated using small angle X‐ray scattering measurements . Very recently it was experimentally demonstrated that aggregates in metalloamphiphile‐in‐organic solutions are not strictly charge neutral …”
Section: Resultsmentioning
confidence: 98%
“…The organic solutions, prepared via liquid‐liquid extraction, contained 0.07 m Ln(NO 3 ) 3 in a 0.5 m N , N ’‐dimethyl‐ N , N ’‐dibutyl tetradecylmalonamide (DMDBTDMA, Scheme S1 in the Supporting Information) n ‐heptane oil phase, along with an amount of waters experimentally obtained . The four solutions were studied using all‐atom, explicit‐solvent MD simulations with a polarizable force field.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations